Productivity and Chemical composition of food type soybean in different sowing dates - Gustavo Henrique Freiria; Wilmar Ferreira Lima; Rodrigo Santos Leite; José Marcos Gontijo Mandarino; Josemeyre Bonifácio da Silva; Cassío Egídio Cavenagui Prete (Acta Scientiarum. Agronomy, 2016)
Protein, oil and isoflavones contents can change according to environmental and genetic factors. The food type soybean shows special characteristics, e.g., high protein content and mild flavor. The objective of this study was to investigate the different sowing dates effect on the yield, 100 grains weight, oil, protein and isoflavones contents of food type breeding lines and soybean cultivars and their interactions. Productivity and 100 grains weight varied with sowing dates and soybean genotypes. The protein content ranged from 36.40 to 42.44% and the oil content from 18.29 to 22.71 %.  No significant interaction was found between genotype versus sowing dates to protein content. Protein and oil contents showed a negative correlation. The isoflavones content also varied with sowing dates and soybean genotypes. The cultivar BRS 257 has the highest isoflavones content including β-glucosides, malonyl-glucoside and aglycones forms. The productivity, 100 grains weight, oil, protein and isoflavones contents is genetically determined but is also influenced by sowing date probably due by the temperature during the grain formation stage and by the height of the planting location.